Relation between Spatial Ability and Critical Thinking in Geography Education: A Survey on Student of Senior High School - Putra, Raharjo Ade; Yani, Ahmad; Somatri, Lili (Universitas Muhammadiyah Surakarta, 2019)
The study aims to find out the relationship between the spatial ability and critical thinking ability of the students of the XI SMA Lab School UPI on geography subjects. The study used the ex-post-facto method to find out causal relationships that were not manipulated or were not given treatment by researchers. The subject in this study was a student of XI IPS 3 class at SMA Lab School UPI Bandung. The instrument used is a matter of double choice of spatial ability and a question of multiple choice of critical thinking ability. Based on the results of data analysis concluded that: (1) The average percentage of the student’s spatial ability amounted to 71.9% with high criteria; (2) The average percentage of the student’s critical thinking ability is 70.17% with high criteria; (3) There is a positive relationship between the spatial ability and the critical thinking ability of learners with a significance value of 0.000 and a Pearson correlation 0.760 value at a strong relationship degree level.